ANALYSIS OF IMMUNE RESPONSES ON TRANSGENIC TIGER SHRIMP (Penaeus monodon) AGAINST PATHOGENIC BACTERIUM Vibrio harveyi - Andi Parenrengi; Bunga Rante Tampangallo; Andi Tenriulo (Indonesian Aquaculture Journal, 2014)
Vibriosis is one of main diseases of the black tiger shrimp Penaeus monodon infected by pathogenic bioluminous bacterium Vibrio harveyi that can cause mass mortalities in shrimp culture. The bacteria can also trigger the disease white spot syndrome virus (WSSV). An effort to produce shrimp disease-resistant strains has been done through transgenesis technology with antiviral gene transfection. By this technology, it is expected an increase in the immune response of shrimp in a variety of diseasecausing pathogens. This study aimed to determine the immune responses (total haemocytes, haemocyte differentiation, and phenoloxydase activity) of transgenic tiger shrimp against pathogenic bacterium V. harveyi. Research using completely randomized design, which consists of two treatments and three replications. Test animals being used were transgenic and non-transgenic shrimp with size, weight 3.93±1.25 g and a total length of 7.59±0.87 cm. Treatments being tested were the injection of bacterium V. harveyi (density of 5x106 cfu/mL) of 0.1 mL/individual on transgenic (A) and non-transgenic shrimp (B). Immune response parameters such as total haemocytes, haemocyte differentiation, and phenoloxydase activity were observed on day 1, 3, and 6 days after challenging. Data were analyzed using t-test by SPSS software. The results showed that the total haemocyte of transgenic shrimp was not significantly different (P>0.05) from non-transgenic shrimp, but haemocyte differentiation and phenoloxydase activity were significantly different (P<0.05) especially on sixth days after being exposed to the bioluminescent bacteria. The study results implied that transgenic shrimp has a better immune response compared than non-transgenic shrimp.